Sastra dan Rasa: Cerminan Perilaku Empati dalam Puisi Remaja - Khumaidi Abdillah (CENDEKIA, 2021)
This paper tries to examine the behavior of empathy in poetry by teenagers from the perspective of Sociology of literature using a qualitative approach. In this study, the results showed that there were empathetic behaviors in poetry by teenagers in the form of: 1) paying attention to others, 2) having a sense of sensitivity towards others, and, 3) being able to feel what other people felt. The results of this study indicate that the behavior of empathy in poetry by teenagers tends to be directed to the closest person. Empathy behavior in this teen's poem.